Streamlining Indonesia’s Tax Compliance through Successful e-Bupot Unification: Menyederhanakan Kepatuhan Pajak Indonesia melalui Penyatuan e-Bupot yang Berhasil - Novianti, Dinda; Ernandi, Herman (Indonesian Journal of Law and Economics Review, 2024)
This study examines the calculation, payment, deposit, and reporting of Income Tax 23 for internet rental services at PT. Alif Investama Teknologi Indonesia, following Law PER-24/PJ/2021. Using an interpretive qualitative method, including interviews and data analysis, the research found that the company’s practices align with current regulations. The implementation of e-Bupot Unification was consistent and thorough from January to December 2022, ensuring compliance with tax laws. The findings highlight the importance of keeping up with regulatory changes to facilitate compliance and efficiency. Highlight: Compliance: Practices align with Law PER-24/PJ/2021. Implementation: Consistent e-Bupot Unification from Jan-Dec 2022. Adaptability: Importance of staying updated with tax regulations. Keyword: Income Tax 23, e-Bupot Unification, internet rental services, PT. Alif Investama Teknologi Indonesia, PER-24/PJ/2021